Computer Program "Variable Stars Calculator" (VSCALC) - Breus, V. (Одеські астрономічні публікації, 2017)
The freeware program is introduced, which allows to visualize data, to make periodogram analysis using the algorithm by Lafler and Kinman (1965), to make easier preparation of time series from visual and photographic observations, and to determine argument and signal value at extrema using polynomial fits. The program has been made under supervision of Prof. I.L.Andronov and both DOS and Windows versions are available from the site of the Ukrainian Asociation of Variable Star Observers (Ьйр://иа1}30.роста.ти) and from the software servers http://softbox.ru?a:21€§i:4616 and http://3oftodrom.ru/win/p4995.3html.